2008
DOI: 10.1029/2007ja012728
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for significantly greater N2 Lyman‐Birge‐Hopfield emission efficiencies in proton versus electron aurora based on analysis of coincident DMSP SSUSI and SSJ/5 data

Abstract: The launch of the Defense Meteorological Satellite Program (DMSP) satellite F16 in 2003 provided the first opportunity to analyze extensive sets of high‐quality coincident auroral particle and FUV data obtained by the onboard sensors Special Sensor Ultraviolet Spectrographic Imager (SSUSI) and Special Sensor Auroral Particle Sensor (SSJ/5). Features of interest are Ly α (121.6 nm), Lyman‐Birge‐Hopfield short (LBHS, the SSUSI 140–150 nm channel), and Lyman‐Birge‐Hopfield long (LBHL, 165–180 nm). We report on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
161
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(165 citation statements)
references
References 39 publications
4
161
0
Order By: Relevance
“…The excitation of the N 2 Rydberg-valence states responsible for these emissions occurs in the short wavelength portion of the EUV between 800 and 1000 Å. This excitation, emission, and associated dissociation and ionization play a role in establishing the physical composition of the N 2 -bearing atmospheres of Earth (Meier et al 2005;Meier & Picone 1994;Knight et al 2008;Strickland et al 1999Strickland et al , 2004aStrickland et al , 2004b, Titan (Ajello et al 2007(Ajello et al , 2011bStevens et al 1994Stevens et al , 2011Stevens 2001;Broadfoot et al 1981;Fulchignoni et al 2005), Triton (Broadfoot et al 1989;Summers & Strobel 1991), and Pluto (Zhu et al 2014;Stern et al 2008;Bagenal et al 1997), and in interstellar clouds and extrasolar protoplanetary disks (Maret et al 2006;Pascucci et al 2009;Li et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The excitation of the N 2 Rydberg-valence states responsible for these emissions occurs in the short wavelength portion of the EUV between 800 and 1000 Å. This excitation, emission, and associated dissociation and ionization play a role in establishing the physical composition of the N 2 -bearing atmospheres of Earth (Meier et al 2005;Meier & Picone 1994;Knight et al 2008;Strickland et al 1999Strickland et al , 2004aStrickland et al , 2004b, Titan (Ajello et al 2007(Ajello et al , 2011bStevens et al 1994Stevens et al , 2011Stevens 2001;Broadfoot et al 1981;Fulchignoni et al 2005), Triton (Broadfoot et al 1989;Summers & Strobel 1991), and Pluto (Zhu et al 2014;Stern et al 2008;Bagenal et al 1997), and in interstellar clouds and extrasolar protoplanetary disks (Maret et al 2006;Pascucci et al 2009;Li et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Knight et al [2008] reported unexpectedly high efficiencies of LBH emission for proton precipitation, higher than predicted by current models. The earliest measurements of LBH excitation by H + impact on N 2 were obtained by energy loss spectroscopy (from 20 to 120 keV by Schowengerdt and Park [1970] and from 0.6 to 4 keV by Moore [1972]).…”
Section: Introductionmentioning
confidence: 60%
“…[4] The 2003 launch of the Defense Meteorological Satellite Program (DMSP) F16 satellite, which contains, among its suite of sensors, Special Sensor Auroral Particle Sensor (SSJ/5) and Special Sensor Ultraviolet Spectrographic Imager (SSUSI) [e.g., Paxton et al, 1992aPaxton et al, , 1992b made it possible, for the first time, to undertake extensive statistical studies of auroral output at far ultraviolet (FUV) wavelengths as a function of auroral input of energetic electrons and ions [Knight et al, 2008; J. T. Correira et al, A downward revision of a recently reported proton auroral LBH emission efficiency, submitted to Journal of Geophysical Research, 2010]. Independently, FUV can also be used to infer the solar energy input [e.g., Strickland et al, 2007] and also determine characteristics of auroral particles that deposit energy in the thermosphere [e.g., Strickland et al, 1993;Germany et al, 1994aGermany et al, , 1994bLummerzheim et al, 1991].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations